Production and operations management : a life cycle approach - Chase, Richard B.; Aquilano, Nicholas J. (Homewood, Ill. : R.D. Irwin, 1985)
In writing this book the authors have attempted to summarize the best of current practice in OM in a way that will allow you to use the material on your first job and as a reference as you progress to other jobs over the next few years. Reasonable effort with the material will get you to the point of practical application of 90 percent of the concepts in this book.
Includes bibliographical references and index.
hza 20/07/2018
Loan
Keywords: Production management; Operation management